Development of Physics Teaching Materials on Rectilinear Motion Material Using the Contextual Teaching Learning Model - Ritonga, Fina Aulia; Rahmatsyah, R (Journal of Indonesian Science Teachers, 2024)
The research aims to produce physics teaching materials regarding rectilinear motion that are suitable for application to class X students at SMA 1 Limapuluh and determine student responses and the effectiveness of the teaching materials developed. The research subjects were class X Science 4 students at SMAN 1 Limapuluh, totaling 32 students. This type of research uses research and development (R&D) with a 4D model. The research instrument consisted of a validation questionnaire for material experts and media experts, teacher response questionnaires, and student responses to physics teaching materials based on Contextual Teaching Learning (CTL). The results of data analysis obtained an average material expert validation of 90.67 with appropriate criteria, media expert validation obtained an average result of 91.60 with appropriate criteria. The validation results of educational practitioners by physics teachers obtained an average result of 90.81 with appropriate criteria. Student responses in the small group test got an average result of 80.07 with very good criteria and the large group test got an average result of 83.28 with very good criteria. The level of effectiveness of teaching materials was obtained from students' pretest and posttest scores with an N-Gain of 0.67 as a medium criterion. Overall, it is concluded that the CTL-based physics teaching materials developed are feasible and effective for increasing students' understanding of physics learning.